The role of social support in pandemic-related stress among university students - Sari, Liliyana; Khaira, Fathiyyatul (International Journal of Research in Counseling and Education, 2021)
The COVID-19 pandemic lockdown has negatively impacted various aspects of university students’ lives which often leads to higher levels of stress. The current research aims to investigate the role of social support in pandemic-related stress among this population. A total of 121 university students in West Sumatra was recruited through convenience sampling to complete the Multidimensional Scale of Perceived Social Support and Pandemic-Related Perceived Stress Scale. The results showed that perceived social support had a significant role in reducing pandemic-related stress by 10.8% in which perceived support from friends was a better predictor than other sources of support. In addition, this study reported a significant difference in pandemic-related stress based on the income of parents where students from lower-income families had a higher prevalence of stress. The findings of this study propose that providing social support particularly from peers would hinder the perceived stress level of university students during the COVID-19 pandemic.